2017
DOI: 10.1182/blood-2017-02-767467
|View full text |Cite
|
Sign up to set email alerts
|

Patients with light-chain amyloidosis and low free light-chain burden have distinct clinical features and outcome

Abstract: The validated criteria of hematologic response in light-chain (AL) amyloidosis are based on the measurement of circulating free light chains (FLCs). Patients with a difference between involved and uninvolved FLC (dFLC) <50 mg/L cannot be assessed for response and are excluded from clinical trials. We compared the clinical characteristics and outcome of 203 newly diagnosed patients with dFLC <50 mg/L (low dFLC) with 866 patients with measurable dFLC (high dFLC) evaluated between 2004 and 2015. Heart involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 29 publications
0
80
0
2
Order By: Relevance
“…In evaluable patients, HR was assessed using validated criteria 16 . Patients who had difference in involved and uninvolved free light chains (dFLC) <5 mg/dL were assessed for response by criteria of complete response (CR) only, based on recent data [22][23][24] . Organ involvement and response were assessed by using existing criteria as described in supplementary data 16,[25][26][27] .…”
Section: Response Assessmentmentioning
confidence: 99%
“…In evaluable patients, HR was assessed using validated criteria 16 . Patients who had difference in involved and uninvolved free light chains (dFLC) <5 mg/dL were assessed for response by criteria of complete response (CR) only, based on recent data [22][23][24] . Organ involvement and response were assessed by using existing criteria as described in supplementary data 16,[25][26][27] .…”
Section: Response Assessmentmentioning
confidence: 99%
“…Our findings are in line with prior reports from our group as well as others, which demonstrate that patients with very small light chain burden (dFLC <50 mg/l) or low light chain burden (dFLC <196 mg/l) are more likely to have renal involvement. (Kumar et al , ; Dittrich et al , ; Milani et al , ; Sidana et al , ) In another series of 77 systemic AL amyloid patients with renal involvement, Wong et al () observed median dFLC levels 127 mg/l, with 60% of patients in this series having co‐existing cardiac involvement. Similarly, Kastritis et al () described a series of 125 patients with renal involvement, of whom 42% had co‐existing cardiac involvement.…”
Section: Discussionmentioning
confidence: 67%
“…Measurable FLCs (ie, a dFLC $50 mg/L) were present in 29 patients (85%); in 4 patients, baseline dFLC was .20 mg/L, and these patients were also evaluable for response. 37,38 In Table 1, the characteristics of the patients are depicted in more detail.…”
Section: Resultsmentioning
confidence: 99%